Encyclopedia of emotion - Reevy, Gretchen (Gale virtual reference library, 2010)
Topics include the neurological foundations of emotional function, competing theories of emotion, multicultural perspectives on emotions, emotional disorders, their diagnosis and treatment. Provides profiles of important organizations and key figures who have shaped our understanding of how and why we feel the way we do.